Challenges of non-face-to-face physiotherapy care in the pandemic of COVID-19 - Alcantara, Sara Fernanda Sousa (2021)
Introduction: The world is currently experiencing a pandemic caused by a new coronavirus (SARS-CoV-2), which causes coronavirus disease disease 2019 (COVID-19). Due to its high transmissibility several economic and health activities were suspended. The physiotherapeutic science was not immune. The Federal Council of Physiotherapy and Occupational Therapy authorized non-face-to-face care in the modalities of teleconsultation, teleconsulting and telemonitoring. The aim of this work is to seek in the literature the challenges of non-face-to-face physiotherapy care in the context of the COVID-19 pandemic. Methodology: This is a literature review, which was obtained through a bibliographic survey and analysis of the relevant articles on the subject. Result: the studies used in the construction of this article state in their entirety positive results in the application of non-face-to-face care through teleconsultations. Conclusion: Telessaúde has been an important alternative for health professionals to ensure the follow-up of their patients in real time in this period of pandemic COVID-19.  However, this tool has negative aspects such as the limitation of access to quality technology and Internet, among other aspects. Thus, physical therapy care in a remote way is faced with significant challenges that must be studied in depth and the use of low-health may be more proficient in the very near future.